Polyimide film, metal-clad laminate and circuit substrate
By increasing the biphenyl skeleton monomer residue content and laminated structure in the polyimide film, the problem of reducing the adhesion of the polyimide film in high temperature environment is solved, and low dielectric loss tangent and long-term heat-resistant resistance are achieved The combination of connection is suitable for circuit substrates in high-speed transmission and high-temperature environments.
Patent Information
- Application Number
- CN202011021751.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-28
- Filing Date
- 2020-09-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-09-25
AI Technical Summary
The existing polyimide films are less adhesive in high temperature environments, making it difficult to take into account low dielectric loss tangent and long-term heat resistance. Especially in the application of flexible printed substrates, the wiring layer is easily caused by high temperature. Adhesion to the insulating resin layer is reduced and peeled off.
By increasing the content ratio of biphenyl skeleton monomer residues in the polyimide layer, combining the laminated structure of the non-thermoplastic and thermoplastic polyimide layers, the oxygen transmittance and thermal expansion coefficient are controlled to form excellent thermal adhesion resistance polyimide film.
It realizes the maintenance of low dielectric loss tangent and long-term thermal bonding in high-temperature environments, and is suitable for circuit substrate applications in high-speed transmission and high-temperature environments.
Smart Images

Figure CN112571901B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polyimide film, a metal-clad laminate and a circuit substrate. Background Art
[0002] Polyimide resin has the characteristics of high insulation, dimensional stability, easy formability, light weight, etc., and is therefore widely used in electronics, electrical equipment or electronic parts as materials for circuit substrates, etc. Particularly, in recent years, with the high performance and high functionality of electrical and electronic equipment, high-speed transmission of information is required, and for the parts or components used in these, high-speed transmission is also required. About the polyimide material for such purposes, low dielectric constant and low dielectric loss tangent are being attempted to be realized, so as to have electrical characteristics for high-speed transmission.
[0003] Most of the prior art related to the low dielectric constant / low dielectric loss tangent of polyimide materials mainly includes the multilayering of resins with low dielectric constant / low dielectric loss tangent (fluorine resins, liquid crystal polymers, etc.), or the deployment of fillers with low dielectric constant / low dielectric loss tangent, etc., and the introduction of composites, porosity, and ester structures of different materials. However, regarding composites or porosity, there are problems such as reduced processability, and regarding the technology of introducing ester structures, there is a problem that it cannot be used in large quantities due to reduced film strength.
[0004] In addition, Patent Documents 1 and 2 propose a polyimide film that can be applied to a high-frequency circuit board by improving dielectric properties through studying the raw material monomer structure of polyimide.
[0005] On the other hand, in recent years, circuit boards have been used in environments exceeding 150° C. For example, flexible printed circuits (FPCs) used in automotive electronic devices are sometimes repeatedly exposed to high-temperature environments of about 150° C.
[0006] In addition, in devices other than vehicle-mounted electronic devices, such as notebook personal computers or supercomputers with a central processing unit (CPU) capable of high-speed processing, the use of flexible printed circuit boards is also increasing in order to achieve further miniaturization and lightness. In such devices, the flexible printed circuit board is repeatedly exposed to a high temperature environment due to the heat generated by the CPU. The representative main cause of the deterioration of the flexible printed circuit board caused by use in a high temperature environment is the floating or peeling of the wiring layer caused by the reduced adhesion between the wiring layer and the insulating resin layer.
[0007] In view of this background, it is expected that flexible printed circuit boards will need to achieve both low dielectric loss tangent and heat-resistant adhesion (maintaining peel strength retention) in high temperature environments in the future. In particular, due to changes in the use environment, heat-resistant adhesion will be required to be maintained for a longer period than before.
[0008] [Prior art literature]
[0009] [Patent Document]
[0010] [Patent Document 1] WO 2017 / 159274
[0011] [Patent Document 2] WO 2018 / 061727 Summary of the invention
[0012] [Problems to be solved by the invention]
[0013] Therefore, an object of the present invention is to provide a polyimide film which can achieve both low dielectric loss tangent and excellent long-term heat-resistant adhesiveness, and which is unlikely to deteriorate in adhesion to a metal layer even when repeatedly exposed to a high-temperature environment.
[0014] [Technical means to solve the problem]
[0015] The inventors of the present invention have conducted intensive research and found that by increasing the content ratio of monomer residues having a biphenyl skeleton in the polyimide constituting the polyimide layer, it is possible to achieve both low dielectric loss tangent of a polyimide film having multiple polyimide layers stacked thereon and excellent long-term heat-resistant adhesion brought about by suppressing oxygen permeability, thereby completing the present invention.
[0016] That is, the polyimide film of the present invention includes a non-thermoplastic polyimide layer and a thermoplastic polyimide layer. The non-thermoplastic polyimide layer includes a non-thermoplastic polyimide. The thermoplastic polyimide layer is laminated on at least one side of the non-thermoplastic polyimide layer and includes a thermoplastic polyimide.
[0017] The polyimide film of the present invention satisfies the following conditions (i) to (iii).
[0018] (i) The thermal expansion coefficient is within the range of 10 ppm / K to 30 ppm / K.
[0019] (ii) Oxygen permeability is 5.5×10 -14 mol / (m 2 ·s·Pa) or less.
[0020] (iii) The ratio of the monomer residue having a biphenyl skeleton calculated by the following formula (1) is 50 mol % or more relative to all monomer residues derived from all monomer components constituting the non-thermoplastic polyimide and the thermoplastic polyimide.
[0021] [Formula 1]
[0022]
[0023] In formula (1), M i is the ratio (unit: mol%) of the monomer residues having a biphenyl skeleton in all the monomer residues derived from all the monomer components in the polyimide constituting the i-th polyimide layer, L i is the thickness of the i-th polyimide layer (unit: μm), L is the thickness of the polyimide film (unit: μm), and n is an integer greater than or equal to 2.
[0024] The polyimide film of the present invention may satisfy not only the above conditions (i) to (iii) but also the following condition (iv).
[0025] (iv) The ratio of the monomer residues having a biphenyl skeleton in all the monomer residues derived from all the monomer components in the thermoplastic polyimide is 30 mol % or more.
[0026] The total thickness of the polyimide film of the present invention may be in the range of 30 μm to 60 μm. In this case, the ratio T2 / T1 of the total thickness T2 of the thermoplastic polyimide layer to the total thickness T1 of the polyimide film may be 0.17 or less.
[0027] The metal-clad laminate of the present invention is a metal-clad laminate comprising an insulating resin layer and a metal layer provided on at least one side of the insulating resin layer. In addition, the metal-clad laminate of the present invention: the insulating resin layer has a thermoplastic polyimide layer in contact with the surface of the metal layer and an indirectly laminated non-thermoplastic polyimide layer, and includes any of the polyimide films.
[0028] The circuit substrate of the present invention is a circuit substrate comprising an insulating resin layer and a wiring layer provided on at least one side of the insulating resin layer. Furthermore, the circuit substrate of the present invention: the insulating resin layer has a thermoplastic polyimide layer in contact with the wiring layer and an indirectly laminated non-thermoplastic polyimide layer, and includes any of the polyimide films.
[0029] [Effects of the Invention]
[0030] The polyimide film of the present invention has a content of monomer residues having a biphenyl skeleton of 50 mol% or more, thereby suppressing oxygen permeability, and achieving both low dielectric loss tangent and improved long-term heat-resistant adhesiveness. Therefore, by using the polyimide film of the present invention as a circuit substrate material, a circuit substrate that can cope with high-speed transmission and maintain adhesion to a metal layer for a long period of time even in a use environment repeatedly exposed to a high-temperature environment can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic cross-sectional view showing the structure of a polyimide film according to an embodiment of the present invention.
[0032] Figure 2 This is a schematic cross-sectional view showing another structural example of the polyimide film according to the embodiment of the present invention.
[0033] [Explanation of Symbols]
[0034] 100, 101: Polyimide film
[0035] 110: Non-thermoplastic polyimide layer
[0036] 120A, 120B: Thermoplastic polyimide layer
[0037] T1, T2A, T2B, T3: Thickness DETAILED DESCRIPTION
[0038] Next, embodiments of the present invention will be described.
[0039] [Polyimide film]
[0040] The polyimide film of one embodiment of the present invention is a polyimide film having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer, wherein the non-thermoplastic polyimide layer includes a non-thermoplastic polyimide, and the thermoplastic polyimide layer is laminated on at least one side of the non-thermoplastic polyimide layer and includes a thermoplastic polyimide. Here, the so-called "non-thermoplastic polyimide" refers to a polyimide having a storage elastic modulus of 1.0×10 at 30° C. measured using a dynamic viscoelasticity measuring device (Dynamic Mechanical Analyzer (DMA)). 9 The storage elastic modulus in the temperature range of 1.0×10 8 The term "thermoplastic polyimide" refers to a polyimide having a storage elastic modulus of 1.0×10 9 The storage elastic modulus in the temperature range of 1.0×10-8 Polyimide of Pa.
[0041] Figure 1 and Figure 2 A structural example of the polyimide film according to the present embodiment is shown. Figure 1 The polyimide film 100 shown has a two-layer structure in which a thermoplastic polyimide layer 120A is laminated on one surface of a non-thermoplastic polyimide layer 110 . Figure 2 The polyimide film 101 shown is a three-layer structure in which a thermoplastic polyimide layer 120A is laminated on one side of a non-thermoplastic polyimide layer 110 and a thermoplastic polyimide layer 120B is laminated on the other side. Figure 1 , Figure 2 The illustrated laminated structure may include, for example, four or more polyimide layers.
[0042] The resin component of the non-thermoplastic polyimide layer 110 preferably includes non-thermoplastic polyimide, and the resin component of the thermoplastic polyimide layers 120A and 120B preferably includes thermoplastic polyimide. When the polyimide films 100 and 101 are laminated with metal foil to form a metal-clad laminate, the metal foil may be laminated on one side or both sides of the thermoplastic polyimide layers 120A and 120B.
[0043] In addition, both the non-thermoplastic polyimide and the thermoplastic polyimide contain an acid dianhydride residue and a diamine residue as “monomer residues.” The “acid dianhydride residue” refers to a tetravalent group derived from tetracarboxylic dianhydride, and the “diamine residue” refers to a divalent group derived from a diamine compound.
[0044] In the polyimide films 100 and 101 of the present embodiment, the non-thermoplastic polyimide layer 110 constitutes a polyimide layer with low thermal expansion, and the thermoplastic polyimide layers 120A and 120B constitute a polyimide layer with high thermal expansion. The polyimide layer with low thermal expansion refers to a polyimide layer whose coefficient of thermal expansion (CTE) is preferably in the range of 1ppm / K or more and 25ppm / K or less, and more preferably in the range of 3ppm / K or more and 25ppm / K or less. In addition, the polyimide layer with high thermal expansion refers to a polyimide layer whose CTE is preferably in the range of 35ppm / K or more, more preferably in the range of 35ppm / K or more and 80ppm / K or less, and further preferably in the range of 35ppm / K or more and 70ppm / K or less. A polyimide layer with a desired CTE can be made by appropriately changing the combination, thickness, and drying / hardening conditions of the raw materials used.
[0045] The polyimide films 100 and 101 of the present embodiment satisfy the following conditions (i) to (iii).
[0046] (i) The thermal expansion coefficient is within the range of 10 ppm / K to 30 ppm / K.
[0047] Regarding the polyimide films 100 and 101 of the present embodiment, when used as an insulating resin layer of a circuit board, for example, in order to prevent the occurrence of warpage or the reduction of dimensional stability, it is important that the coefficient of thermal expansion (CTE) of the entire film is within the range of 10 ppm / K to 30 ppm / K, preferably within the range of 10 ppm / K to 25 ppm / K, and more preferably within the range of 15 ppm / K to 25 ppm / K. If the CTE is less than 10 ppm / K or exceeds 30 ppm / K, warpage will occur or dimensional stability will be reduced.
[0048] (ii) Oxygen permeability is 5.5×10 -14 mol / (m 2 ·s·Pa) or less.
[0049] By controlling the oxygen permeability of the polyimide films 100 and 101 to 5.5×10 -14 mol / (m 2 ·s·Pa) or less. For example, when used as an insulating resin layer of a circuit board, even if repeatedly exposed to a high temperature environment, the adhesion to the wiring layer can be maintained for a long period of time, and excellent long-term heat-resistant adhesion can be obtained. The oxygen permeability of the polyimide film 100, 101 exceeds 5.5×10 -14 mol / (m 2 ·s·Pa), for example, when an insulating resin layer used as a circuit board is repeatedly exposed to high temperatures, the oxidation of the wiring layer is promoted by oxygen penetrating through the insulating resin layer, and the adhesion between the wiring layer and the insulating resin layer is reduced.
[0050] (iii) The ratio of monomer residues having a biphenyl skeleton (hereinafter sometimes referred to as "residues containing a biphenyl skeleton") calculated by the following formula (1) to all monomer residues derived from all monomer components constituting the non-thermoplastic polyimide and the thermoplastic polyimide is 50 mol% or more.
[0051] [Formula 2]
[0052]
[0053] In formula (1), M i is the ratio (unit: mol%) of the residue containing a biphenyl skeleton in all the monomer residues derived from all the monomer components in the polyimide constituting the i-th polyimide layer, Li is the thickness of the i-th polyimide layer (unit: μm), L is the thickness of the polyimide film (unit: μm), and n is an integer greater than or equal to 2.
[0054] Relative to all monomer residues derived from all monomer components of the polyimide constituting the polyimide films 100 and 101, the ratio of the residue containing the biphenyl skeleton calculated by formula (1) is 50 mol% or more, thereby easily forming an ordered structure in the polymer as a whole by the rigid structure derived from the monomer, reducing the oxygen permeability, and the dielectric loss tangent can be reduced by suppressing the movement of molecules. If the ratio of the residue containing the biphenyl skeleton is less than 50 mol%, the dielectric loss tangent is not sufficiently reduced. In addition, if the thickness of the polyimide film is thinned, the oxygen permeability is not sufficiently reduced. Therefore, for example, when used in a circuit substrate, the long-term heat-resistant adhesion is insufficient and it is difficult to adapt to high-speed transmission. From the point of view of the above, the ratio of the residue containing the biphenyl skeleton calculated by formula (1) is preferably 60 mol% or more, more preferably 65 mol% or more. On the other hand, in order to maintain the physical properties required for the polyimide film used as a circuit substrate material, the ratio of the residue containing the biphenyl skeleton calculated by formula (1) is preferably set to 80 mol% or less.
[0055] Here, as shown in the following formula (a), the biphenyl skeleton is a skeleton formed by two phenyl groups being single-bonded. Therefore, examples of the residue containing the biphenyl skeleton include biphenyldiyl and biphenyltetrayl. The aromatic ring contained in these residues may have any substituent.
[0056] As a representative example of biphenyl diyl, a group represented by the following formula (b) can be cited. As a representative example of biphenyl tetrayl, a group represented by the following formula (c) can be cited. Furthermore, in biphenyl diyl and biphenyl tetrayl, the bonding bond in the aromatic ring is not limited to the position shown in formula (b) and formula (c), and as mentioned above, the aromatic ring contained in these residues may have any substituent.
[0057] [Chemistry 1]
[0058]
[0059] The residue containing a biphenyl skeleton is a structure derived from a raw material monomer, and may be derived from an acid dianhydride or a diamine compound.
[0060] Representative examples of acid dianhydride residues having a biphenyl skeleton include residues derived from acid dianhydrides such as 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA), 2,3',3,4'-biphenyl tetracarboxylic dianhydride, and 4,4'-bisphenol-bis(trimellitic anhydride). Among these, acid dianhydride residues derived from BPDA (hereinafter also referred to as "BPDA residues") are preferred because they are easy to form an ordered structure of a polymer and can reduce dielectric loss tangent or hygroscopicity by inhibiting the movement of molecules. In addition, BPDA residues can impart self-supporting properties to the gel film of polyamic acid, which is a polyimide precursor.
[0061] Representative examples of diamine compounds having a biphenyl skeleton include diamine compounds having only two aromatic rings, such as 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-diethyl-4,4'-diaminobiphenyl (m-EB), 2,2'-diethoxy-4,4'-diaminobiphenyl (m-EOB), 2,2'-dipropoxy-4,4'-diaminobiphenyl (m-POB), 2,2'-di-n-propyl-4,4'-diaminobiphenyl (m-POB), 2,2'-di-n-propyl-4,4'-diaminobiphenyl (m-EB), 2,2'-diethoxy-4,4'-diaminobiphenyl (m-EOB), 2,2'-dipropoxy-4,4'-diaminobiphenyl (m-POB), 2,2'-di-n-propyl-4,4'-diaminobiphenyl (m-POB), 2,2'-di-n-propyl-4,4'-diaminobiphenyl (m-POB), 2,2'-di-n-propyl-4,4'-diaminobiphenyl (m-EB), 2,2'-di- biphenyl, m-NPB), 2,2'-divinyl-4,4'-diamino biphenyl (VAB), 4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl (TFMB), etc. The residues derived from these diamine compounds have a rigid structure and have the function of giving an ordered structure to the polymer as a whole. By containing the residues derived from these diamine compounds, a polyimide with low oxygen permeability and low hygroscopicity can be obtained, which can reduce the moisture inside the molecular chain, thereby reducing the dielectric loss tangent.
[0062] It is preferable that the polyimide films 100 and 101 of this embodiment further satisfy the following condition (iv) in addition to satisfying the above conditions (i) to (iii).
[0063] (iv) The ratio of the residue containing a biphenyl skeleton in all the monomer residues derived from all the monomer components in the thermoplastic polyimide is 30 mol% or more.
[0064] The ratio of the residues containing a biphenyl skeleton in all the monomer residues constituting the thermoplastic polyimide is 30 mol% or more, thereby forming an ordered structure in the entire polymer through the rigid structure derived from the monomer, so that a polyimide having low oxygen permeability and hygroscopicity, excellent long-term heat-resistant adhesion, and low dielectric loss tangent can be obtained despite being thermoplastic. Furthermore, when the thermoplastic polyimide layers 120A and 120B are provided on both sides of the non-thermoplastic polyimide layer 110, it is sufficient that any one of the thermoplastic polyimide layers 120A and 120B satisfies the condition (iv), but it is preferred that both thermoplastic polyimide layers 120A and 120B satisfy the condition (iv).
[0065] <Thickness>
[0066] The overall thickness T1 of the polyimide films 100 and 101 of the present embodiment can be set within a specified range according to the purpose of use, for example, preferably within the range of 30 μm to 60 μm, and more preferably within the range of 35 μm to 50 μm. If the thickness T1 does not meet the lower limit, it is difficult to sufficiently reduce the oxygen permeability, and there is a concern that the adhesion between the wiring layer and the insulating resin layer will be reduced when repeatedly exposed to high temperatures. On the other hand, if the thickness T1 exceeds the upper limit, the following undesirable conditions will occur: when the polyimide film is bent, cracks will be generated and it will break, etc.
[0067] In addition, the total thickness T2 (here, T2 refers to Figure 1 T2A Figure 2 The ratio T2 / T1 of T2A+T2B) to the overall thickness T1 of the polyimide films 100 and 101 is preferably 0.17 or less, more preferably in the range of 0.10 to 0.15. If the value of the ratio is greater than 0.17, the oxygen permeability becomes large, and the dielectric loss tangent is difficult to reduce. Therefore, when used in a circuit substrate, for example, the long-term heat-resistant adhesiveness is insufficient, and it is difficult to adapt to high-speed transmission.
[0068] The lower limit of the ratio T2 / T1 is not particularly limited. The reason is that the smaller the ratio T2 / T1 is, the easier it is to achieve a reduction in oxygen permeability and dielectric loss tangent. Among them, the smaller the ratio T2 / T1 is, the smaller the thickness ratio occupied by the thermoplastic polyimide layers 120A and 120B is. Therefore, the lower limit of the ratio T2 / T1 is preferably about 0.02 as a value that can ensure the bonding reliability of the polyimide films 100 and 101 and the wiring layer.
[0069] Furthermore, the thickness T3 of the non-thermoplastic polyimide layer 110 can be set within a predetermined range according to the purpose of use, for example, preferably within a range of 25 μm to 49 μm, and more preferably within a range of 30 μm to 49 μm. If the thickness T3 does not meet the lower limit, the improvement effect of the dielectric properties of the polyimide films 100 and 101 becomes small, and the oxygen permeability becomes large. When repeatedly exposed to high temperatures, there is a concern that the adhesion between the wiring layer and the insulating resin layer is reduced.
[0070] Generally speaking, polyimide can be manufactured by reacting an acid dianhydride with a diamine compound in a solvent to generate a polyamic acid and then heating the polyamic acid for ring closure (imidization). For example, an acid dianhydride and a diamine compound are dissolved in an organic solvent in approximately equimolar amounts, and the polymerization reaction is carried out by stirring for 30 minutes to 24 hours at a temperature in the range of 0°C to 100°C, thereby obtaining a polyamic acid as a precursor of the polyimide. During the reaction, the reaction components are dissolved in a manner such that the generated precursor is in the range of 5% by weight to 30% by weight, preferably in the range of 10% by weight to 20% by weight in the organic solvent. As the organic solvent used in the polymerization reaction, for example, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, cresol, etc. These solvents can also be used in combination of two or more, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. In addition, there is no particular limitation on the amount of such an organic solvent used, but it is preferably used in an amount adjusted to a concentration of about 5% by weight to 30% by weight of the polyamic acid solution obtained by the polymerization reaction.
[0071] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, but can be concentrated, diluted or replaced with other organic solvents as needed. In addition, polyamic acid is generally excellent in solvent solubility, so it can be used advantageously. The viscosity of the solution of polyamic acid is preferably in the range of 500cps to 100,000cps. If it is out of the range, the film is prone to uneven thickness, stripes and other undesirable conditions during the coating operation performed using a coating machine, etc. There is no particular limitation on the method for imidizing the polyamic acid, for example, it can be suitably adopted in the solvent and under the temperature conditions in the range of 80°C to 400°C for 1 hour to 24 hours for heating and other heat treatments.
[0072] Next, non-thermoplastic polyimide and thermoplastic polyimide will be described in more detail.
[0073] <Non-thermoplastic polyimide>
[0074] In the polyimide films 100 and 101, the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 110 contains an acid dianhydride residue and a diamine residue. The non-thermoplastic polyimide preferably contains 60 mol% or more of the residues containing a biphenyl skeleton in all the monomer residues derived from all the monomer components, and more preferably contains 70 mol% or more. By setting the residues containing a biphenyl skeleton in the non-thermoplastic polyimide to 60 mol% or more, the content ratio of the residues containing a biphenyl skeleton in the entire polyimide constituting the polyimide films 100 and 101 can be increased, the oxygen permeability can be reduced, and a low dielectric loss tangent can be achieved.
[0075] (dianhydride residue)
[0076] The non-thermoplastic polyimide preferably contains 35 mol% or more of the acid dianhydride residues having a biphenyl skeleton in all the acid dianhydride residues, more preferably 50 mol% or more, and more preferably contains the above-mentioned amount of biphenyl tetrayl represented by formula (c).
[0077] In addition to the acid dianhydride residue having a biphenyl skeleton, the non-thermoplastic polyimide may also contain the residue of an acid dianhydride commonly used as a raw material for polyimide within a range that does not impair the effect of the invention. Examples of such acid dianhydride residues include pyromellitic dianhydride (PMDA), 1,4-phenylene bis(trimellitic acid monoester) dianhydride (TAHQ), 2,3,6,7-naphthalene tetracarboxylic dianhydride (2,3,6,7-naphthalene tetracarboxylic dianhydride, ... dianhydride, NTCDA), 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride or 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl) ether dianhydride, 3,3",4,4"-p-terphenyl tetracarboxylic dianhydride, 2,3,3",4"-p-terphenyl Tetracarboxylic acid dianhydride or 2,2",3,3"-terphenyltetracarboxylic acid dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-propane dianhydride or 2,2-bis(3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride or bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride or bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride or 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7, 8-phenanthrene-tetracarboxylic dianhydride, 1,2,6,7-phenanthrene-tetracarboxylic dianhydride or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 2,3,5,6-cyclohexane dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-perylene-tetracarboxylic dianhydride, 3,4,9,10-perylene-tetracarboxylic dianhydride, 4,5,10,11-perylene-tetracarboxylic dianhydride or 5,6,11,12-perylene-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,Acid dianhydride residues derived from aromatic tetracarboxylic dianhydrides such as 5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride, and ethylene glycol bis(trimellitic)anhydride.
[0078] (Diamine residue)
[0079] The non-thermoplastic polyimide preferably contains 70 mol% or more of diamine residues having a biphenyl skeleton in all diamine residues, and more preferably contains 85 mol% or more. It is further preferred to contain the biphenyl diyl represented by formula (b) in the above amount. The biphenyl diyl represented by formula (b) has a rigid structure and has the effect of imparting an ordered structure to the polymer as a whole, thereby reducing the oxygen permeability and reducing the dielectric loss tangent by inhibiting the movement of molecules.
[0080] In addition to the diamine residue having a biphenyl skeleton, the non-thermoplastic polyimide may also contain a residue of a diamine compound commonly used as a raw material for polyimide within a range that does not impair the effect of the invention. Examples of such diamine residues include 1,4-diaminobenzene (p-phenylenediamine (p-PDA)), 4-aminophenyl-4'-aminobenzoate (4-aminophenyl-4'-aminobenzoate), benzoate, APAB), 3,3'-diaminodiphenylmethane, 3,3'-diaminodiphenylpropane, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylpropane, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminobenzophenone, (3,3'-bisamino)diphenylamine, 1,4-bis(3-aminophenoxy)benzene, 3-[4-(4-aminophenoxy)phenoxy]aniline, 3-[3-( 4-aminophenoxy) phenoxy] aniline, 1,3-bis(4-aminophenoxy)benzene (1,3-bis(4-aminophenoxy)benzene, TPE-R), 1,3-bis(3-aminophenoxy)benzene (1,3-bis(3-aminophenoxy)benzene, APB), 4,4'-[2-methyl-(1,3-phenylene)bisoxy] dianiline, 4,4'-[4-methyl-(1,3-phenylene)bisoxy] dianiline, 4,4'-[5-methyl-(1,3-phenylene)bisoxy] dianiline, bis[4,4 '-(3-aminophenoxy)]benzanilide, 4-[3-[4-(4-aminophenoxy)phenoxy]phenoxy]aniline, 4,4'-[oxybis(3,1-phenyleneoxy)]dianiline, bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), bis[4-(4-aminophenoxy)phenyl]ketone (BAPS), is[4-(4-aminophenoxy)phenyl]ketone, BAPK), 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane, BAPP), bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoropropane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'-methylenebis-o-toluidine, 4,4'-methylenebis-2,6-dimethylaniline, 4,4'-methylenebis-2,6-diethylaniline, 3,3'-diaminodiphenylethane, 3,3'-diaminobiphenyl, 3,3'-dimethoxybenzidine, 3,3"- Diamino-p-terphenyl, 4,4'-[1,4-phenylenebis(1-methylethylidene)]dianiline, 4,4'-[1,3-phenylenebis(1-methylethylidene)]dianiline, bis(p-aminocyclohexyl)methane, bis(p-β-amino-tert-butylphenyl) ether, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-tert-butyl)toluene, 2, 4-Diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylene diamine, p-xylylene diamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, piperazine, 2'-methoxy-4,4'-diaminobenzanilide, 4,4'-diaminobenzanilide, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis(4-aminophenoxy)- Diamine residues derived from aromatic diamine compounds such as 2,5-di-tert-butylbenzene, 6-amino-2-(4-aminophenoxy)benzoxazole, 2,6-diamino-3,5-diethyltoluene, 2,4-diamino-3,5-diethyltoluene, 2,4-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, and bis(4-amino-3-ethyl-5-methylphenyl)methane; diamine residues derived from aliphatic diamine compounds such as dimer acid-type diamine in which the two terminal carboxylic acid groups of dimer acid are substituted with primary aminomethyl or amino groups, etc.
[0081] In the non-thermoplastic polyimide, by selecting the types of the acid dianhydride residue and the diamine residue, or the respective molar ratios when two or more acid dianhydride residues or diamine residues are used, it is possible to control oxygen permeability, dielectric properties, thermal expansion coefficient, storage elastic modulus, tensile elastic modulus, etc. In addition, in the non-thermoplastic polyimide, when there are a plurality of structural units of polyimide, they may exist in the form of blocks or randomly, but preferably exist randomly.
[0082] The non-thermoplastic polyimide preferably contains an aromatic tetracarboxylic acid residue derived from an aromatic tetracarboxylic dianhydride and an aromatic diamine residue derived from an aromatic diamine. By making both the dianhydride residue and the diamine residue contained in the non-thermoplastic polyimide an aromatic group, the dimensional accuracy of the polyimide films 100 and 101 in a high temperature environment can be improved.
[0083] The imide group concentration of the non-thermoplastic polyimide is preferably 33% by weight or less. Here, "imide group concentration" refers to the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire structure of the polyimide. If the imide group concentration exceeds 33% by weight, the hygroscopicity increases due to the increase in polar groups. By selecting a combination of the acid dianhydride and the diamine compound to control the orientation of the molecules in the non-thermoplastic polyimide, the increase in CTE associated with the reduction in the imide group concentration can be suppressed, thereby ensuring low hygroscopicity.
[0084] The weight average molecular weight of the non-thermoplastic polyimide is preferably in the range of 10,000 to 400,000, and more preferably in the range of 50,000 to 350,000. If the weight average molecular weight is less than 10,000, the strength of the film decreases and the film tends to become brittle. On the other hand, if the weight average molecular weight exceeds 400,000, the viscosity increases excessively, and the film thickness tends to be uneven, streaks, and other undesirable conditions are likely to occur during the coating operation.
[0085] <Thermoplastic polyimide>
[0086] In polyimide films 100, 101, the thermoplastic polyimide constituting thermoplastic polyimide layers 120A, 120B comprises an acid dianhydride residue and a diamine residue. As described in condition (iv), the thermoplastic polyimide preferably contains more than 30 mol% of residues containing biphenyl skeletons in all monomer residues derived from all monomer components, and more preferably contains more than 40 mol%. By setting the residues containing biphenyl skeletons in the thermoplastic polyimide to more than 30 mol%, the content ratio of the residues containing biphenyl skeletons in the entire polyimide constituting the polyimide films 100, 101 can be increased, the oxygen permeability can be reduced, and low dielectric loss tangent can be achieved. On the other hand, regarding thermoplastic polyimide, in order to ensure adhesion to the metal layer, it is necessary to improve the flexibility of the polyimide molecular chain and impart thermoplasticity, so it is preferred that the upper limit of the content of the residues containing biphenyl skeletons is set to less than 65 mol%.
[0087] (dianhydride residue)
[0088] The thermoplastic polyimide preferably contains 60 mol% or more of the acid dianhydride residues having a biphenyl skeleton in all the acid dianhydride residues, and more preferably contains the biphenyl tetrayl group represented by the formula (c) in the above amount.
[0089] The thermoplastic polyimide may contain, in addition to the residue of the acid dianhydride having a biphenyl skeleton, a residue of an acid dianhydride generally used as a raw material for polyimide within a range not impairing the effects of the invention. Examples of such an acid dianhydride residue include the residues of the acid dianhydride exemplified for the non-thermoplastic polyimide.
[0090] (Diamine residue)
[0091] Thermoplastic polyimide preferably contains more than 1 mol% of diamine residues with a biphenyl skeleton in all diamine residues, more preferably more than 5 mol%. Furthermore, it is preferred to be suitable for the biphenyl diyl represented by the formula (b) containing the amount. The biphenyl diyl represented by the formula (b) has a rigid structure and has the effect of imparting an ordered structure to the polymer as a whole, so that the dielectric loss tangent or hygroscopicity can be reduced by suppressing the movement of molecules. Furthermore, by being used as a raw material for thermoplastic polyimide, a polyimide with low oxygen permeability and excellent long-term heat-resistant adhesion can be obtained.
[0092] The thermoplastic polyimide may contain, in addition to the diamine residue having a biphenyl skeleton, a residue of a diamine compound generally used as a raw material for polyimide within a range not impairing the effects of the invention. Examples of such a diamine residue include residues of diamine compounds exemplified for the non-thermoplastic polyimide.
[0093] In the thermoplastic polyimide, by selecting the types of the acid dianhydride residue and the diamine residue, or the respective molar ratios when two or more acid dianhydride residues or diamine residues are used, the thermal expansion coefficient, tensile elastic modulus, glass transition temperature, etc. can be controlled. In addition, in the thermoplastic polyimide, when there are a plurality of polyimide structural units, they may exist in the form of blocks or randomly, but preferably exist randomly.
[0094] The thermoplastic polyimide preferably contains an aromatic tetracarboxylic acid residue derived from an aromatic tetracarboxylic dianhydride and an aromatic diamine residue derived from an aromatic diamine. By making both the dianhydride residue and the diamine residue contained in the thermoplastic polyimide aromatic, degradation of the polyimide films 100 and 101 in a high temperature environment can be suppressed.
[0095] The imide group concentration of the thermoplastic polyimide is preferably 30% by weight or less. Here, "imide group concentration" refers to the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire structure of the polyimide. If the imide group concentration exceeds 30% by weight, the elastic modulus at a temperature above the glass transition temperature is not easy to decrease, and the low hygroscopicity is also deteriorated due to the increase of polar groups.
[0096] The weight average molecular weight of the thermoplastic polyimide is preferably in the range of 10,000 to 400,000, and more preferably in the range of 50,000 to 350,000. If the weight average molecular weight is less than 10,000, the strength of the film decreases and the film tends to become brittle. On the other hand, if the weight average molecular weight exceeds 400,000, the viscosity increases excessively, and the film thickness tends to be uneven, streaks, and other undesirable conditions are likely to occur during the coating operation.
[0097] In the polyimide films 100 and 101, the thermoplastic polyimide layers 120A and 120B function as adhesive layers to improve adhesion with metal layers such as copper foil. Therefore, the glass transition temperature of the thermoplastic polyimide is preferably in the range of 200°C to 350°C, more preferably in the range of 200°C to 320°C.
[0098] Thermoplastic polyimide, for example, becomes an adhesive layer connected to the wiring layer of the circuit board, so in order to suppress the diffusion of copper, it is most preferably a completely imidized structure. Among them, a part of the polyimide can also become an amic acid. The imidization rate is measured by using a Fourier transform infrared spectrophotometer (commercial product: FT / IR620 manufactured by JASCO Corporation) and using the attenuated total reflection (ATR) method to measure the infrared absorption spectrum of the polyimide film, thereby measuring the infrared absorption spectrum of the polyimide film at 1015 cm -1 Based on the benzene ring absorber near 1780cm -1 The absorbance of the C=O expansion and contraction of the imide group was calculated.
[0099] <Polyimide film form>
[0100] The polyimide films 100 and 101 of the present embodiment are not particularly limited as long as they are polyimide films that meet the above conditions, and may be films (sheets) containing insulating resins, for example, films of insulating resins stacked on substrates such as metal foils such as copper foils, glass plates, polyimide films, polyamide films, polyester films, and other resin sheets.
[0101] <Dielectric loss tangent>
[0102] Polyimide film 100,101, for example, in the case of an insulating resin layer used as a circuit substrate, in order to reduce the dielectric loss during high-frequency signal transmission, as a whole film, the dielectric loss tangent (Tanδ) at 10GHz when measured by a separation dielectric resonator (split dielectric resonator (Split Post Dielectric Resonator, SPDR)) is preferably less than 0.004. In order to improve the transmission loss of the circuit substrate, it is particularly important to control the dielectric loss tangent of the insulating resin layer, and the effect of reducing the transmission loss is increased by setting the dielectric loss tangent to the range. Therefore, in the case of using polyimide film 100,101, for example, as an insulating resin layer of a high-frequency circuit substrate, the transmission loss can be efficiently reduced. If the dielectric loss tangent at 10GHz exceeds 0.004, then when using polyimide film 100,101 as an insulating resin layer of a circuit substrate, it is easy to produce undesirable conditions such as the loss of electrical signals on the transmission path of the high-frequency signal becomes larger. The lower limit of the dielectric loss tangent at 10 GHz is not particularly limited, but needs to be considered in terms of physical property control when the polyimide films 100 and 101 are used as insulating resin layers of a circuit board.
[0103] <Dielectric constant>
[0104] When the polyimide films 100 and 101 are used as insulating resin layers of circuit boards, for example, the dielectric constant of the film as a whole at 10 GHz is preferably 4.0 or less in order to ensure impedance matching. If the dielectric constant at 10 GHz exceeds 4.0, when the polyimide films 100 and 101 are used as insulating resin layers of circuit boards, dielectric loss deteriorates, and undesirable conditions such as increased loss of electrical signals in the transmission path of high-frequency signals are likely to occur.
[0105] <Packing>
[0106] The polyimide films 100 and 101 of the present embodiment may also contain inorganic fillers or organic fillers in the non-thermoplastic polyimide layer 110 or the thermoplastic polyimide layers 120A and 120B as needed. Specifically, for example, inorganic fillers such as silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, and calcium fluoride; or organic fillers such as fluorine-based polymer particles or liquid crystal polymer particles. These can be used alone or in combination of two or more. Furthermore, in the case of containing an organic filler, the organic filler is not equivalent to all the monomer components constituting the non-thermoplastic polyimide layer 110 or the thermoplastic polyimide layer 120A and 120B.
[0107] [Method for producing polyimide film]
[0108] As preferred aspects of the method for producing the polyimide films 100 and 101 according to the present embodiment, for example, the following [1] to [3] can be exemplified.
[0109] [1] A method of manufacturing the polyimide films 100 and 101 by repeatedly coating a polyamic acid solution on a supporting substrate and drying the solution multiple times, and then performing imidization.
[0110] [2] A method of manufacturing the polyimide films 100 and 101 by repeatedly coating a polyamic acid solution on a supporting substrate and drying the solution, then peeling off the polyamic acid gel film from the supporting substrate and performing imidization.
[0111] [3] A method of manufacturing the polyimide films 100 and 101 by applying a polyamic acid solution in a multilayered state by multilayer extrusion, drying the solution, and then imidizing the solution (hereinafter referred to as a multilayer extrusion method).
[0112] The method of [1] may include, for example, the following steps 1a to 1c;
[0113] (1a) a step of coating a polyamic acid solution on a supporting substrate and drying the solution;
[0114] (1b) forming a polyimide layer by heat-treating and imidizing polyamic acid on a supporting substrate; and
[0115] (1c) A step of obtaining the polyimide films 100 and 101 by separating the supporting substrate from the polyimide layer.
[0116] The method [2] may include, for example, the following steps 2a to 2c;
[0117] (2a) a step of coating a polyamic acid solution on a supporting substrate and drying the solution;
[0118] (2b) a step of separating the supporting substrate from the gel film of polyamic acid; and
[0119] (2c) A step of obtaining the polyimide films 100 and 101 by heat-treating the gel film of the polyamic acid to imidize it.
[0120] In the method [1] or the method [2], by repeatedly performing step 1a or step 2a a plurality of times, a laminated structure of polyamic acid can be formed on a supporting substrate. Furthermore, there is no particular limitation on the method for coating the polyamic acid solution on the supporting substrate, and for example, coating can be performed using a coating machine such as a notch wheel, a die, a knife, or a die lip.
[0121] The method [3] can be carried out in the same manner as the method [1] or the method [2], except that in step 1a of the method [1] or step 2a of the method [2], the laminated structure of polyamic acid is simultaneously applied by multilayer extrusion and dried.
[0122] The polyimide films 100 and 101 manufactured in this embodiment are preferably imidized with polyamic acid on a supporting substrate. Since the resin layer of polyamic acid is imidized while being fixed on the supporting substrate, the expansion and contraction change of the polyimide layer during the imidization process can be suppressed, thereby maintaining the thickness or dimensional accuracy of the polyimide films 100 and 101.
[0123] [Metal-clad laminate]
[0124] The metal-clad laminate of this embodiment includes an insulating resin layer and a metal layer provided on at least one side of the insulating resin layer, and a part or all of the insulating resin layer can be formed using the polyimide films 100 and 101 of the embodiment. In order to improve the adhesion between the insulating resin layer and the metal layer, the layer in the insulating resin layer that contacts the metal layer can be a thermoplastic polyimide layer 120A or 120B.
[0125] The material of the metal layer is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among them, copper or copper alloys are particularly preferred. Furthermore, the material of the wiring layer in the circuit substrate described later is also the same as that of the metal layer.
[0126] The thickness of the metal layer is not particularly limited. For example, when a metal foil represented by copper foil is used, it is preferably 35 μm or less, and more preferably within the range of 5 μm to 25 μm. From the perspective of production stability and handling properties, the lower limit of the thickness of the metal foil is preferably 5 μm. Furthermore, when copper foil is used, it can be a rolled copper foil or an electrolytic copper foil. In addition, as the copper foil, a commercially available copper foil can be used.
[0127] The metal foil may be subjected to a rust-proofing treatment or a surface treatment for improving adhesion, for example, by siding, aluminum alkoxide, aluminum chelate, silane coupling agent, or the like.
[0128] Next, regarding the metal-clad laminate, a copper-clad laminate in which the metal layer is formed of copper foil is taken as an example and described in more detail. In the copper-clad laminate, the copper foil is provided on one side or both sides of the insulating resin layer. That is, the copper-clad laminate can be a single-sided copper-clad laminate (single-sided CCL (Copper Clad Laminate)) or a double-sided copper-clad laminate (double-sided CCL).
[0129] The copper-clad laminate can be produced, for example, by preparing a resin film composed of the polyimide films 100 and 101 of the above-described embodiment, sputtering a metal thereon to form a seed layer, and then forming a copper foil layer by, for example, copper plating.
[0130] Alternatively, a copper-clad laminate can be produced by preparing a resin film composed of the polyimide films 100 and 101 of the above-described embodiment and laminating a copper foil thereon by a method such as thermocompression bonding.
[0131] Furthermore, the copper-clad laminate can also be produced by casting a coating liquid containing a polyamic acid as a precursor of polyimide on a copper foil, drying the coating film, and then heat-treating the film for imidization to form a polyimide layer.
[0132] [Circuit board]
[0133] The metal-clad laminate of the above-described embodiment is effectively used mainly as a circuit board material for FPC, etc. The circuit board as one embodiment of the present invention can be manufactured by processing the metal layer of the metal-clad laminate into a pattern to form a wiring layer by a conventional method.
[0134] That is, the circuit substrate of this embodiment includes an insulating resin layer and a wiring layer provided on at least one side of the insulating resin layer, and a part or all of the insulating resin layer can be formed using the polyimide films 100 and 101 of the embodiment. In addition, in order to improve the adhesion between the insulating resin layer and the wiring layer, the layer in the insulating resin layer that contacts the wiring layer can be a thermoplastic polyimide layer 120A, 120B.
[0135] [Example]
[0136] The following examples are shown to more specifically describe the features of the present invention. However, the scope of the present invention is not limited to the examples. Furthermore, in the following examples, unless otherwise specified, various measurements and evaluations are based on the following contents.
[0137] [Viscosity measurement]
[0138] The viscosity at 25° C. was measured using an E-type viscometer (Brookfield, trade name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the value when the viscosity stabilized was read 2 minutes after the start of the measurement.
[0139] [Measurement of glass transition temperature (Tg)]
[0140] The glass transition temperature was measured using a dynamic viscoelasticity measuring device (DMA: manufactured by UBM, trade name: E4000F) from 30°C to 400°C at a heating rate of 4°C / min and a frequency of 11 Hz for a polyimide film of 5 mm×20 mm in size, and the temperature at which the elastic modulus change (tan δ) was the maximum was defined as the glass transition temperature. The storage elastic modulus at 30°C measured using DMA was 1.0×10 9 The storage elastic modulus in the temperature range of 1.0×10- 8 Pa is defined as "thermoplastic", and the storage elastic modulus at 30°C is 1.0×10 9 The storage elastic modulus in the temperature range of 1.0×10 8 The case of Pa or more is regarded as "non-thermoplastic".
[0141] [Determination of coefficient of thermal expansion (CTE)]
[0142] Using a thermomechanical analyzer (manufactured by Bruker, trade name: 4000SA), a load of 5.0 g was applied to a polyimide film of size 3 mm × 20 mm, and the temperature was raised from 30°C to 265°C at a certain heating rate, and then maintained at the temperature for 10 minutes, and then cooled at a rate of 5°C / min to determine the average thermal expansion coefficient (thermal expansion coefficient) from 250°C to 100°C.
[0143] [Determination of moisture absorption rate]
[0144] Two polyimide film test pieces (width: 4 cm x length: 25 cm) were prepared and dried at 80°C for 1 hour. Immediately after drying, they were placed in a constant temperature and humidity room at 23°C / 50% RH and left to stand for more than 24 hours. The weight change before and after was calculated using the following formula.
[0145] Moisture absorption rate (weight %) = [(weight after moisture absorption - weight after drying) / weight after drying] × 100
[0146] [Determination of dielectric constant and dielectric loss tangent]
[0147] The dielectric constant and dielectric loss tangent of the polyimide film at a frequency of 10 GHz were measured using a vector network analyzer (manufactured by Agilent, trade name: E8363C) and a separated dielectric resonator (SPDR resonator). The material used in the measurement was left for 24 hours under the conditions of temperature: 24°C to 26°C and humidity: 45% to 55%.
[0148] [Calculation of Imide Group Concentration]
[0149] The value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) by the molecular weight of the entire structure of the polyimide was defined as the imide group concentration.
[0150] [Measurement of surface roughness of copper foil]
[0151] The surface roughness of the copper foil was measured in a tapping mode within an area of 80 μm × 80 μm on the surface of the copper foil using an atomic force microscope (AFM) (manufactured by Bruker AXS, trade name: Dimension Icon Scanning Probe Microscopy (SPM)) and a probe (manufactured by Bruker AXS, trade name: TESPA (NCHV), tip curvature radius of 10 nm, spring constant 42 N / m). The ten-point average roughness (Rzjis) was calculated.
[0152] [Determination of oxygen permeability]
[0153] The oxygen permeability was measured at a temperature of 23°C ± 2°C and a humidity of 65% RH ± 5% RH according to the differential pressure method of Japanese Industrial Standards (JIS) K7126-1. As vapor permeability measuring devices, GTR-30XAD2 manufactured by GTR Technology (TECH) and G2700T·F manufactured by Yanako Technical Science were used.
[0154] [Measurement of initial peel strength]
[0155] The copper foil of the copper-clad laminate (copper foil / multi-layer polyimide layer) was processed with a circuit at a width of 1 mm in the direction of resin coating at intervals of 10 mm, and then cut into width: 8 cm × length: 4 cm. The peel strength was measured by using a Tensilon Tester (manufactured by Toyo Seiki Seisaku-sho, trade name: Strograph VE-1D), fixing the polyimide layer of the cut test sample on an aluminum plate with double-sided tape, peeling the circuit-processed copper foil at a speed of 50 mm / min in a 180° direction, and obtaining the median strength when peeling 10 mm from the polyimide layer, which was set as the initial peel strength.
[0156] [Determination of peel strength after heating]
[0157] The copper foil of the copper-clad laminate (copper foil / multi-layer polyimide layer) was processed with a circuit with a width of 1 mm at intervals of 10 mm in the direction of resin coating, and then cut into width: 8 cm × length: 4 cm. The cut sample was stored in a hot air oven set at 150°C (under atmospheric environment) and taken out after 1000 hours. The peel strength was measured using a Tensilon Tester (manufactured by Toyo Seiki Seisaku-sho, Ltd., trade name: Strograph VE-1D). The polyimide layer of the sample taken out was fixed on an aluminum plate with double-sided tape, and the copper foil processed with the circuit was peeled off at a speed of 50 mm / min in the 180° direction to obtain the central value strength when 10 mm was peeled off from the polyimide layer.
[0158] [Measurement of Thickness of Polyimide Layer]
[0159] For copper-clad laminates, a ferric chloride aqueous solution is used to etch and remove the copper foil to obtain a polyimide film. The obtained polyimide film is cut into short strips, resin embedded, and then cut in the film thickness direction using a microtome to make ultrathin sections of about 100 nm. For the produced ultrathin sections, the STEM function of a scanning electron microscope (SEM) (SU9000) manufactured by Hitachi High-technologies is used to observe at an accelerating voltage of 30 kV, and the thickness of each polyimide layer is measured at 5 points, and its average value is set as the thickness of each polyimide layer.
[0160] The abbreviations used in Examples and Reference Examples represent the following compounds.
[0161] PMDA: Pyromellitic Dianhydride
[0162] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0163] m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl
[0164] TPE-R: 1,3-bis(4-aminophenoxy)benzene
[0165] TPE-Q: 1,4-bis(4-aminophenoxy)benzene
[0166] DAPE: 4,4'-diaminodiphenyl ether
[0167] PDA: p-phenylenediamine
[0168] BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane
[0169] Dianiline-P: 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene (manufactured by Mitsui Chemicals Fine Chemicals Co., Ltd., trade name: Dianiline-P)
[0170] DDA: C36 aliphatic diamine (manufactured by Croda Japan, trade name: PRIAMINE 1074, amine value: 210 mgKOH / g, mixture of dimer diamines of cyclic structure and chain structure, content of dimer component: 95 wt % or more)
[0171] DMAc: N,N-dimethylacetamide
[0172] (Synthesis example 1)
[0173] Under nitrogen gas flow, 12.061 g of m-TB (0.0568 mol), 0.923 g of TPE-Q (0.0032 mol), 1.0874 g of dianiline-P (0.0032 mol), and DMAc in an amount such that the solid content concentration after polymerization becomes 15% by weight were added to a 300 ml separable flask, and stirred and dissolved at room temperature. Next, after adding 6.781 g of PMDA (0.0311 mol) and 9.147 g of BPDA (0.0311 mol), stirring was continued for 3 hours at room temperature and polymerization reaction was performed to obtain a polyamic acid solution a. The solution viscosity of the polyamic acid solution a was 29,800 cps.
[0174] Secondly, the polyamic acid solution a is evenly applied on the copper foil 1 (electrolytic copper foil, thickness: 12 μm, surface roughness Rzjis on the resin side: 2.1 μm) so that the thickness after hardening becomes about 25 μm, and then the solvent is removed by heating and drying at 120°C. Furthermore, a staged heat treatment is performed from 120°C to 360°C within 30 minutes to complete imidization. For the obtained copper-clad laminate, an aqueous solution of ferric chloride is used to etch and remove the copper foil, thereby preparing a polyimide film a (non-thermoplastic, Tg: 316°C, moisture absorption rate: 0.61% by weight). In addition, the imide group concentration of the polyimide constituting the polyimide film a is 31.6% by weight.
[0175] (Synthesis example 2)
[0176] Under nitrogen flow, 11.825 g of m-TB (0.0557 mol), 0.905 g of TPE-Q (0.0031 mol), 1.653 g of DDA (0.0031 mol), and DMAc in an amount such that the solid content concentration after polymerization becomes 15% by weight were added to a 300 ml separable flask, and stirred and dissolved at room temperature. Next, after adding 6.649 g of PMDA (0.0305 mol) and 8.968 g of BPDA (0.0305 mol), stirring was continued for 3 hours at room temperature to perform polymerization reaction, thereby obtaining a polyamic acid solution b. The solution viscosity of the polyamic acid solution b was 27,800 cps.
[0177] Secondly, the polyamic acid solution b is evenly applied on the copper foil 1 so that the thickness after hardening becomes about 25 μm, and then the solvent is removed by heating and drying at 120°C. Furthermore, a staged heat treatment is performed from 120°C to 360°C within 30 minutes to complete imidization. For the obtained copper-clad laminate, an aqueous solution of ferric chloride is used to etch and remove the copper foil to prepare a polyimide film b (non-thermoplastic, Tg: 258°C, moisture absorption rate: 0.54% by weight). In addition, the imide group concentration of the polyimide constituting the polyimide film b is 30.9% by weight.
[0178] (Synthesis example 3)
[0179] Under nitrogen flow, 11.920 g of m-TB (0.0562 mol) and 2.897 g of TPE-Q (0.0099 mol) and DMAc in an amount such that the solid content concentration after polymerization becomes 15 wt % were added to a 300 ml separable flask, and stirred and dissolved at room temperature. Next, 11.354 g of PMDA (0.0521 mol) and 3.829 g of BPDA (0.0130 mol) were added, and the mixture was stirred for 3 hours at room temperature to carry out polymerization reaction, thereby obtaining a polyamic acid solution c. The solution viscosity of the polyamic acid solution c was 31,200 cps.
[0180] Secondly, the polyamic acid solution c is evenly applied on the copper foil 1 so that the thickness after hardening becomes about 25 μm, and then the solvent is removed by heating and drying at 120°C. Furthermore, a staged heat treatment is performed from 120°C to 360°C within 30 minutes to complete imidization. For the obtained copper-clad laminate, an aqueous solution of ferric chloride is used to etch and remove the copper foil, thereby preparing a polyimide film c (non-thermoplastic, Tg: 375°C, moisture absorption rate: 0.81% by weight). In addition, the imide group concentration of the polyimide constituting the polyimide film c is 33.2% by weight.
[0181] (Synthesis Example 4)
[0182] Under nitrogen flow, 1.548 g of PDA (0.0143 mol) and 11.465 g of DAPE (0.0573 mol) and DMAc in an amount such that the solid content concentration after polymerization becomes 15% by weight were added to a 300 ml separable flask, and stirred and dissolved at room temperature. Next, after adding 10.764 g of PMDA (0.0494 mol) and 6.223 g of BPDA (0.0212 mol), stirring was continued for 3 hours at room temperature to carry out polymerization reaction, thereby obtaining a polyamic acid solution d. The solution viscosity of the polyamic acid solution d was 23,500 cps.
[0183] Next, the polyamic acid solution d was cast from the slit of a T-die mold so that the thickness after hardening was 25 μm, and extruded on a smooth band-shaped metal support in a drying furnace to form a film, heated at 130° C. for a predetermined time, and then peeled off from the support to obtain a self-supporting film. Furthermore, the two ends of the self-supporting film in the width direction were held and inserted into a continuous heating furnace, and the film was heated and imidized under the condition of from 100° C. to a maximum heating temperature of 380° C., thereby preparing a polyimide film d (non-thermoplastic, Tg:>400° C., moisture absorption rate: 1.14% by weight). In addition, the imide group concentration of the polyimide constituting the polyimide film d was 36.2% by weight.
[0184] (Synthesis Example 5)
[0185] Under nitrogen flow, 15.591 g of BAPP (0.0380 mol) and DMAc in an amount such that the solid content concentration after polymerization becomes 12% by weight were added to a 300 ml separable flask, stirred and dissolved at room temperature. Next, 8.409 g of PMDA (0.0386 mol) was added, and the mixture was stirred for 3 hours at room temperature to carry out polymerization reaction, thereby obtaining a polyamic acid solution e. The solution viscosity of the polyamic acid solution e was 2,350 cps.
[0186] Secondly, the polyamic acid solution e is evenly coated on the copper foil 1 so that the thickness after hardening is about 10 μm, and then the solvent is removed by heating and drying at 120°C. Furthermore, a staged heat treatment is performed from 120°C to 360°C within 30 minutes to complete imidization. For the obtained copper-clad laminate, an aqueous solution of ferric chloride is used to etch and remove the copper foil to prepare a polyimide film e (thermoplastic, Tg: 320°C, moisture absorption rate: 0.55% by weight). In addition, the imide group concentration of the polyimide constituting the polyimide film e is 23.6% by weight.
[0187] (Synthesis Example 6)
[0188] Under nitrogen flow, 1.847 g of m-TB (0.0087 mol) and 10.172 g of TPE-R (0.0348 mol) and DMAc in an amount such that the solid content concentration after polymerization becomes 12% by weight were added to a 300 ml separable flask, and stirred and dissolved at room temperature. Next, after adding 2.889 g of PMDA (0.0132 mol) and 9.092 g of BPDA (0.0309 mol), stirring was continued for 3 hours at room temperature to perform polymerization reaction, thereby obtaining a polyamic acid solution f. The solution viscosity of the polyamic acid solution f was 2,210 cps.
[0189] Secondly, the polyamic acid solution f is evenly applied on the copper foil 1 so that the thickness after hardening is about 10 μm, and then the solvent is removed by heating and drying at 120°C. Furthermore, a staged heat treatment is performed from 120°C to 360°C within 30 minutes to complete imidization. For the obtained copper-clad laminate, an aqueous solution of ferric chloride is used to etch and remove the copper foil to prepare a polyimide film f (thermoplasticity, Tg: 226°C, moisture absorption rate: 0.41% by weight). In addition, the imide group concentration of the polyimide constituting the polyimide film f is 27.4% by weight.
[0190] [Example 1]
[0191] Polyamic acid solution f is uniformly applied on copper foil 2 (electrolytic copper foil, thickness: 12 μm, surface roughness Rzjis on the resin side: 0.6 μm) so that the thickness after curing becomes 2.5 μm, and then heated and dried at 120°C for 1 minute to remove the solvent. Polyamic acid solution a is uniformly applied on the resulting product so that the thickness after curing becomes 25 μm, and then heated and dried at 120°C for 3 minutes to remove the solvent. Furthermore, polyamic acid f is uniformly applied on the resulting product so that the thickness after curing becomes 2.5 μm, and then heated and dried at 120°C for 1 minute to remove the solvent. Thereafter, a staged heat treatment is performed from 140°C to 360°C to complete imidization, thereby preparing a copper-clad laminate 1.
[0192] The initial peel strength and the peel strength after heating were measured using the obtained copper-clad laminate 1, and the results were 1.06 kN / m and 0.69 kN / m, respectively.
[0193] The copper foil of the copper-clad laminate 1 was etched away using an aqueous solution of ferric chloride to obtain a polyimide film 1a. The obtained polyimide film 1a was evaluated for CTE, dielectric properties, and oxygen permeability. The results were CTE: 22 ppm / K, dielectric constant: 3.56, dielectric loss tangent: 0.0032, and oxygen permeability: 4.59×10 -14 mol / (m 2The measurement results are shown in Table 2.
[0194] [Examples 2 to 4, Comparative Example 1, and Reference Examples 1 and 2]
[0195] Except for using the polyamic acid solution described in Table 1 and changing the thickness structure, copper-clad laminates 2 to 4, 5, 6 to 7 and polyimide films 2a to 4a, 5a and 6a to 7a of Examples 2 to 4, Comparative Example 1 and Reference Example 1 to 2 were obtained in the same manner as in Example 1. The measurement results are shown in Tables 1 and 2.
[0196] [Table 1]
[0197]
[0198] [Table 2]
[0199]
[0200] Comparative Example 2
[0201] The polyamic acid solution d is cast from the slit of the T-die die in such a way that the thickness becomes 30 μm after curing, and is extruded on a smooth belt-shaped metal support in a drying furnace to form a thin film, heated at 130°C for a predetermined time, and then peeled off from the support to obtain a self-supporting film. Furthermore, while the self-supporting film is continuously transported, the polyamic acid solution e is applied to the atmospheric surface of the self-supporting film using a die coater so that the thickness becomes 2.5 μm after curing, and dried in a drying furnace at 120°C for a predetermined time. Subsequently, for the surface opposite to the surface coated with the polyamic acid solution e, the polyamic acid solution e is also applied in the same manner as described above so that the thickness becomes 2.5 μm after curing, and dried in a drying furnace at 120°C for a predetermined time.
[0202] The two ends of the self-supporting film in the width direction are held and inserted into a continuous heating furnace, and the film is heated and imidized at a temperature from 100° C. to a maximum heating temperature of 380° C., thereby obtaining a polyimide film 8b. A copper foil is overlapped on one side of the polyimide film 8b, and a Teflon (registered trademark) film is overlapped on the other side, and the two are heat-pressed for 15 minutes at a temperature of 320° C. and a pressure of 340 MPa. After the pressing, the Teflon (registered trademark) film is peeled off, thereby preparing a copper-clad laminate 8.
[0203] The initial peel strength and the peel strength after heating were measured using the obtained copper-clad laminate 8, and the results were 1.15 kN / m and 1.01 kN / m, respectively.
[0204] The copper foil of the copper-clad laminate 8 was etched away in the same manner as in Example 1 to obtain a polyimide film 8a. The obtained polyimide film 8a was evaluated for CTE, dielectric properties, and oxygen permeability. The results were CTE: 22 ppm / K, dielectric constant: 3.65, dielectric loss tangent: 0.0073, and oxygen permeability: 1.17×10 -14 mol / (m 2 ·s·Pa).
[0205] As mentioned above, although embodiment of this invention was described in detail for the purpose of illustration, this invention is not limited to the said embodiment, Various deformation|transformation is possible.
Claims
1. A polyimide film comprising a non-thermoplastic polyimide layer and a thermoplastic polyimide layer, wherein the non-thermoplastic polyimide layer comprises a non-thermoplastic polyimide, and the thermoplastic polyimide layer is laminated on at least one side of the non-thermoplastic polyimide layer and comprises a thermoplastic polyimide; and the polyimide film is characterized in that: the following conditions (i) to (iii), condition (v) and condition (vi) are satisfied; (i) a coefficient of thermal expansion in the range of 10 ppm / K to 30 ppm / K; (ii) Oxygen permeability is 4.59×10 -14 mol / (m 2 ·s·Pa) or less; (iii) the ratio of monomer residues having a biphenyl skeleton calculated by the following formula (1) relative to all monomer residues derived from all monomer components constituting the non-thermoplastic polyimide and the thermoplastic polyimide is 60 mol% or more; (v) the overall thickness of the polyimide film is in the range of 30 μm to 60 μm; (vi) a ratio T2 / T1 of the total thickness T2 of the thermoplastic polyimide layer to the overall thickness T1 of the polyimide film is 0.17 or less; In formula (1), M i is the ratio of the monomer residue having a biphenyl skeleton in all the monomer residues derived from all the monomer components in the polyimide constituting the i-th polyimide layer, mol%, L i is the thickness of the i-th polyimide layer in μm, L is the thickness of the polyimide film in μm, and n is an integer greater than or equal to 2.
2. The polyimide film according to claim 1, characterized in that: In addition to satisfying the conditions (i) to (iii), condition (v) and condition (vi), the following condition (iv) is also satisfied; (iv) The ratio of the monomer residues having a biphenyl skeleton in all the monomer residues derived from all the monomer components in the thermoplastic polyimide is 30 mol % or more.
3. A metal-clad laminate comprising an insulating resin layer and a metal layer provided on at least one side of the insulating resin layer, wherein: The insulating resin layer has a thermoplastic polyimide layer in contact with the surface of the metal layer and a non-thermoplastic polyimide layer laminated indirectly thereon, and includes the polyimide film according to claim 1 .
4. A circuit substrate comprising an insulating resin layer and a wiring layer provided on at least one side of the insulating resin layer, wherein: The insulating resin layer includes a thermoplastic polyimide layer in contact with the wiring layer and a non-thermoplastic polyimide layer laminated indirectly thereon, and includes the polyimide film according to claim 1 .